ANALISIS POTENSI KECURANGAN (FRAUD) PENGELOLAAN DANA DESA DI DESA RUKTI SEDYO KECAMATAN RAMAN UTARA KABUPAATEN LAMPUNG TIMUR - Wahyudi Jaya Kusuma; Suyanto Suyanto; Nedi Hendri (Universitas Muhammadiyah Metro, 2021)
The purpose of this study was to identify the potential for fraud in village management. This study uses an approach approach and the type of data used is primary data obtained directly by using interview techniques to the Technical Officer of Village Financial Management (PTPKD) Rukti Sedyo Village, North Raman District, East Lampung Regency. The results of the study indicate that in the financial management of Rukti Sedyo Village there are potential vulnerabilities, including: an act of doing something, disciplinary behavior, feeling that it does not harm others and considers mistakes as a natural thing. Lack of training and supervision of the village fund management process can lead to a deviation that can be detrimental, training is carried out to improve the ability of village officials in managing village funds, this is very necessary to create a good management of village funds and in accordance with the rules that have been set.